2021
DOI: 10.1101/2021.07.12.21259864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of SARS-Cov-2-specific memory B cells six months after vaccination with BNT162b2 mRNA vaccine

Abstract: SARS-CoV-2 mRNA vaccines have demonstrated high efficacy and immunogenicity, but limited information is currently available on memory B cells generation and long-term persistence. Here, we investigated Spike-specific memory B cells and humoral responses in 145 subjects, up to six months after the BNT162b2 vaccine (Comirnaty) administration. Spike-specific antibody titers peaked 7 days after the second dose and significant titers and neutralizing activity were still observed after six months, despite a progress… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A previous study showed that fully-vaccinated individuals have protection against COVID-19 of more than 80% [ 9 ]. Not only induce immunogenicity, but a study also reported that the mRNA vaccine enhances memory B cells function for six months [ 33 ]. Following this assumption, in this study, full vaccination efficacy was 47.3% against chronic cough, 68.3% against chronic headache, and 71.5% against arthritis and remained consistent when treating the outcomes as interval censored-response (45.8%, 66.3%, and 60.9%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that fully-vaccinated individuals have protection against COVID-19 of more than 80% [ 9 ]. Not only induce immunogenicity, but a study also reported that the mRNA vaccine enhances memory B cells function for six months [ 33 ]. Following this assumption, in this study, full vaccination efficacy was 47.3% against chronic cough, 68.3% against chronic headache, and 71.5% against arthritis and remained consistent when treating the outcomes as interval censored-response (45.8%, 66.3%, and 60.9%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A time-dependent modulation of the B cell response has been observed, with B cell phenotypes changing from CD27 + IgD + IgM + CXCR5 + cells to both IgA + or IgG + (CD27 + IgD - CD38 + CXCR5 - CD11c + ) 7 days after the second dose, and then differentiating into MBC (CD27 + IgD - CD38 + CXCR5 + CD24 + CD11c - ) at longer time points ( 31 ). Several distinct antigen-specific MBC populations emerged postvaccination with varying kinetics.…”
Section: Role Of the B Cell Response Elicited By Vaccinationmentioning
confidence: 99%
“…Using multiparametric flow cytometry analysis, we and other groups have identified spike-specific cells in the blood induced by vaccination with mRNA BNT162b2 vaccine and we have tracked their persistence up to 6 months after vaccine administration ( 31 , 32 ). The presence of molecules specific for different states of antigen-specific B-cell differentiation, allows to identify and distinguish plasmablasts, detectable very early after vaccine administration, from MBC.…”
Section: Assays To Measure the B Cell Immune Responsesmentioning
confidence: 99%
See 2 more Smart Citations